PENGARUH PERAWATAN PIJAT OKETANI TERHADAP KELANCARAN ASI PADA IBU POSTPARTUM DI WILAYAH KERJA PUSKESMAS SUNGAI RUMBAI - Evin Noviana Sari; Rati Purwati; Putri Retno Naliza (Ensiklopedia of Journal, 2025)
Oketani massage is a breast treatment first popularized by Sotomi Oketani from Japan and has been implemented in several countries including Japan, Korea and India. Sotomi explained that breastfeeding can increase the closeness between mother and baby. Oketani massage aims to increase the smoothness of breast milk production and is one way to stimulate the pectoral muscles of the breast which makes the breasts elastic. This study aims to determine the effect of breast care with the Oketani massage technique on the smoothness of breast milk in postpartum mothers in the working area of the Sungai Rumbai Community Health Center. The study was conducted in May 2025 using a pre-experimental method with a One Group Pre-Test Post-Test design. The sample consisted of 10 postpartum mothers who experienced problems in breast milk production. The results of the analysis using the Wilcoxon test showed a p-value of 0.004 (p 0.05), which means there is a significant effect between before and after Oketani massage. Before the intervention, 80% of respondents experienced irregular breast milk production, while after the intervention, all respondents showed smoothness. This study revealed that the most effective Oketani massage is done 2-5 times per day with the intensity of Oketani massage regularly for 3 days because in the first three days postpartum breast milk has not come out due to the lack of stimulation of the hormones prolactin and oxytocin, so it can be concluded that Oketani massage is effective in increasing the smooth production of breast milk in postpartum mothers.Keywords: Oketani Massage, Postpartum, Breast Milk Production